Pengembangan Media Wayang Dongeng untuk Meningkatkan Keterampilan Berbicara pada Siswa Kelas III SD - Miyatna Sari, Nurul Azizah; ERY RAHMAWATI; Sari, Anggra Lita Sandra Dewi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
In this research is the students’ limited ability to retell reading texts orally, which is caused by the use of conventional teaching methods or lecture-based instruction supported only by Indonesian language textbooks. This study employed a Research and Development (R&D) method using the ADDIE model, involving 23 third-grade students of SDN Kebonsari 62 Candi in the 2025/2026 academic year. The data were collected through expert validation sheets and speaking skill tests in the form of pretests and posttests. The results of material validation showed an average score of 4.75, categorized as very valid, while the media validation results showed an average score of 3.94, categorized as valid. Furthermore, the speaking skill test results indicated a significant improvement in students’ performance, with the average pretest score increasing from 9.21 to an average posttest score of 15.21, and an average class N-gain score of 0.58, which falls into the moderate category. These findings demonstrate that the storybook puppet media is feasible and effective for use in Indonesian language learning to enhance students’ speaking skills. Keywords: folktale puppet, speaking skills, learning media development.